Building Innovation in Islamic Education Management through Collegial Collective Leadership at the Darussalam Gontor Modern Islamic Boarding School in Ponorogo - Nur Ali; Ahmad Fadhil; Jamarusdi; Malkayanti S. Sangadji; Moh Ali (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
The leadership model is one of the most important elements and really determines the success of Islamic education management, especially Islamic boarding schools. The right model will encourage leadership effectiveness. There are two models, namely individual leadership and collegial collective. Facts and data show that the individual model often has the potential to give rise to internal conflict and lead to the decline or even extinction of the Islamic boarding school after the founding kiai leaves, especially if the status of the institution has not been endowed and its cadres lack loyalty. The collegial collective leadership model at Pondok Modern Darussalam Gontor (PMDG) Ponorogo has proven to be effective in enhancing educational quality based on the values, structure, and culture of the pesantren. This study aims to examine the innovative strategies implemented by Gontor in improving educational quality through a systematic and sustainable collaborative leadership approach. The findings reveal that collective leadership—characterized by the principles of devolution of power, empowerment, shared decision-making, and shared leadership—has fostered a strong organizational culture, high cadre loyalty, and continuity in quality management. Data collection used interview, observation and documentation techniques with descriptive qualitative methods based on literature review and primary documentation.